A Media-Theoretical Armamentarium - Scott Wark; Yigit Soncul (Media Theory, 2022)
This essay provides an introductory account of the concept of pharmakon and its uses in different traditions relevant to media theory. First, we chart existing media-theoretical uses of the pharmakon and the main points of reference in this body of work, such as Plato, Jacques Derrida and Bernard Stiegler. Second, we present the alternative genealogies of the pharmakon in reference to material, chemical and medical contexts. Taking the approach Galen developed to the pharmakon in the context of medical practice in Classical antiquity as its guide, this section presents an alternate history of the concept in order to illustrate how else it might be conceived and used. Finally, we introduce the contributions to this special issue which, as a whole, explicate a range of “pharmacologies” and “pharmacologics” available to media theory.